2014
DOI: 10.1177/0025802414557880
|View full text |Cite
|
Sign up to set email alerts
|

Variability of footprint ridge density and its use in estimation of sex in forensic examinations

Abstract: The present study deals with a comparatively new biometric parameter of footprints called footprint ridge density. The study attempts to evaluate sex-dependent variations in ridge density in different areas of the footprint and its usefulness in discriminating sex in the young adult population of north India. The sample for the study consisted of 160 young adults (121 females) from north India. The left and right footprints were taken from each subject according to the standard procedures. The footprints were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…The present study shows the mean ridge density of great toe for female (R: 10.20, L:10.49) is comparatively higher than male (R: 9.98, L: 10.82). While study on great toe ridge density among North Indian population from Himanchal Pradesh State showed the mean ridge density in female (R: 8.1, L: 7.7) to be higher than male (R:6.4, L:7.0) 21 . Another toe print study was conducted onIban population in Malaysia Borneo showed that the mean ridge density of great toe for males (R: 12.6, L:12.9) are comparatively lower than females (R:13.5, L:13.4) 24 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The present study shows the mean ridge density of great toe for female (R: 10.20, L:10.49) is comparatively higher than male (R: 9.98, L: 10.82). While study on great toe ridge density among North Indian population from Himanchal Pradesh State showed the mean ridge density in female (R: 8.1, L: 7.7) to be higher than male (R:6.4, L:7.0) 21 . Another toe print study was conducted onIban population in Malaysia Borneo showed that the mean ridge density of great toe for males (R: 12.6, L:12.9) are comparatively lower than females (R:13.5, L:13.4) 24 .…”
Section: Discussionmentioning
confidence: 89%
“…Literature review shows that many studies have been conducted on fi ngerprint [17][18] and palm print [19][20] ridge density for gender determination, but there are limited study conducted on the footprint [21][22][23] and toe printridge density 4,24 . In most of the crime scenes, partial footprints are commonly found rather than complete footprint.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from the automated black-white percentage were better but still relatively poor. Ridge counting for each sampled image square followed the procedure of Krishan et al [ 25 ] and [ 26 ] was then used as a further test. Using the data for 168 participants, 29 footprints were excluded due to being faint, an average total ridge count for females were obtained of 52 versus 47 for males across the three squares.…”
Section: Resultsmentioning
confidence: 99%
“…The sexing from footprint ridge density is based upon the fact that the females possess finer ridge details than males and hence, the females have more ridges than the males in a defined area of a footprint. In this regard, only two studies [100,101] are available on sexing from footprint ridge density which show a sexing potential of about 82.6-83.6% and 77.7-91.5%, respectively.…”
Section: Friction Ridge Analysis Of the Plantar Surface In Identificamentioning
confidence: 99%